The effect of 6 prism base-out during smartphone use on vergence and accommodation systems - Wan Harun, Maryam Aliya; Ithnin, Mohd. Hafidz (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: Prism is used in binocular vision assessment and visual therapy. The short-term use of prism, particularly base-out prism on vergence and accommodation system, was not well-explained in the previous investigations. Aim: This current study aimed to assess the effect of 6 prism base-out for 15 minutes on vergence and accommodation system during the utilization of smartphone. Methodology: Thirty normal participants were recruited in this quasi-experimental study. All participants wore 6 prism-base out for 15 minutes while using smartphone at 40cm. Near positive fusional vergence (PFV) and amplitude of accommodation (AA) were measured before and after 15 minutes of 6 prism base-out wear during smartphone usage. Results: The results showed no significant difference for both parameters measured when comparison was made between before and after prism base-out inducement in front of eye. Conclusion: The vergence and accommodation systems presented in this study were almost identical among normal subjects after inducement of 6 prism base-out for 15 minutes during watching smartphone.